Structure, Electronic, and Vibrational properties of Salbutamol using Quantum Chemical and Molecular Docking Approaches - Joshi, Dipak; Joshi, Bhawani Datt (Api Journal of Science, 2025)
Molecular structure, vibrational spectra, electronic properties, and receptor bindingmechanism Salbutamol, a short-acting β₂-adrenergic agonist used in asthma therapy,were studied using density functional theory (DFT) and molecular docking methods. The molecular geometry was optimized at the DFT/B3LYP/3-21G level of theory. Thecalculated rotational constants are A = 0.917 GHz, B = 0.209 GHz, and C = 0.182 GHzprovide insights into the molecular moments of inertia. The HOMO-LUMO energy gapwas found to be 5.14 eV in the gas phase, decreasing in polar solvents, which indicated enhanced electronic polarization. Time-dependent DFT (TD-DFT) simulations revealedstrong π→π* electronic transitions in the near-ultraviolet region. Molecular docking ofSalbutamol into thebinding site of the human β₂-adrenergic receptor (PDB ID: 3NY8)yielded a binding affinity of -7.545 kcal/mol. The docking pose shows that Salbutamolforms hydrogen bonds with ASP113 and ASN312, and engages in hydrophobic contactswith VAL114, VAL117, and PHE290. These structural and electronic insights rationalizethe known biological activity of Salbutamol and may guide the future design of improved β₂-agonist drugs.